Mortality Following Surgical Management of Vancouver B Periprosthetic Fractures. (January 2017) - Gitajn, Ida Leah; Heng, Marilyn; Weaver, Michael J.; Casemyr, Natalie; May, Collin; Vrahas, Mark S.; Harris, Mitchel B.
Abstract : Objectives: The goals of this study are to evaluate mortality after Vancouver B periprosthetic fractures and determine predictors of mortality; compare mortality among patients with loose femoral stems treated with revision arthroplasty versus fixation alone; compare mortality among patients with radiographically "indeterminate" fractures treated with revision or fixation; and evaluate the rate of return to surgery for patients who underwent revision compared with fixation. Design: Retrospective study. Setting: Three academic level 1 trauma centers. Patients/Participants: Two hundred three patients treated for Vancouver B periprosthetic fractures. Intervention: N/A. Main Outcome Measurements: The primary outcome measure was mortality. The secondary outcome measure was reoperation because of infection, failure of fixation, dislocation, or other mechanical failure. Results: Overall 1-year survival was 87% and 5-year survival was 54%. Among patients with loose femoral stems, there was no significant difference with regard to survival between patients treated with fracture fixation or revision arthroplasty (1-year survival 83% vs. 85%, 5-year survival 41% vs. 58%). Among patients whose radiographs were classified as indeterminate, there was no significant difference between patients treated with fracture fixation alone or revision arthroplasty. There was no significant difference between total reoperation rates between the two groups (11% vs. 16%). Conclusion: This study suggests that there is no discernible survival benefit to treating patients with periprosthetic fractures with either revision arthroplasty or fixation alone. Therefore, from a mortality perspective, when faced with Vancouver B periprosthetic fractures, the orthopaedic surgeon should feel comfortable performing the type of intervention he/she is most proficient to perform. Level of Evidence: Prognostic level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.